Impact of the SWOT Strategy and Mind Maps on Teaching Chess in Developing Certain Mental Abilities and Reflective Thinking in Females Aged 14–16 Years - Muhammad Suhail Najm (Physical Activity Journal (PAJU), 2025)
The study aims to develop two educational programs based on the SWOT matrix and mind mapping to teach chess tactics and examine these programs' impact on enhancing specific mental abilities and reflective thinking. Due to the experimental approach being appropriate for the study's nature, the researcher used it. Academically talented first-year intermediate female students from five different schools in Mosul made up the research population. The total number of students was 560. Al-Mosul High School was randomly selected to conduct the main experiment. The school included 130 students distributed across three classes: Class (A) with 40 students, Class (B) with 45 students, and Class (C) with 45 students. Class (C) was designated the first group (experimental) through a lottery system, taught using the SWOT matrix. Class (B) was defined as the second experimental group taught using the mind mapping strategy. Class (A) served as the control group, which was taught using the traditional method. Meanwhile, Al-Hadbaa Secondary School was used to conduct the pilot experiments. The researcher adopted an equivalent group design. The instructional lessons for the three research groups lasted for (20) instructional units, with two units per week, over a duration of (10) weeks. The statistical analysis was conducted using the various methods. According to the findings, students in the first experimental group—who were instructed using the SWOT matrix—performed better than those in the second experimental group and the control group in every area of attention and associated times. Additionally, the students in the second group (experimental), who were taught using mind mapping, outperformed the students in the first experimental group and the control group in all reflective thinking skills